Feminism and Religion: How Faiths View Women and Their Rights - Paludi, Michele Antoinette (Women's Psychology Series, 2016)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Epigraph -- Contents -- Series Foreword -- Foreword -- Acknowledgments -- Introduction -- Part I Views from the Bible and Buddhism to the Quran and Taoism -- Chapter 1 Is Faith in the Bible and Feminism Compatible? -- Chapter 2 The Goddess-Worshipping Age: Feminist Egalitarianism in Prehistory and Early History -- Chapter 3 Feminist Perspectives from the Hebrew Bible -- Chapter 4 The Church, Woman, Leadership, and the Body -- Chapter 5 Feminism Re-frames Who Wrote Hebrew Scriptures: 10th-Century Tamar, the "Master" Storyteller -- Chapter 6 Women in the Holy Quran -- Chapter 7 Feminism in Hinduism: Female Deities and Their Influence on South Asian Culture -- Chapter 8 Feminism in Buddhism -- Chapter 9 Femineity in the Gospel of John -- Chapter 10 Feminism in the Eastern Orthodox Church -- Chapter 11 The Mystical Feminine in Baha'i Scriptures -- Part II Religious Philosophy in Feminism and Feminist Action -- Chapter 12 Martial Religion, Ravaging Warfare, and Rape: Polytheistic Greek and Monotheistic Israelite Views -- Chapter 13 Judaism and Feminism -- Chapter 14 A Room Prepared: Women and the Mystic Experience -- Chapter 15 The Feminine Spiritual -- Chapter 16 Feminism and the Pro-Life/Pro-Choice Debate -- Chapter 17 Historical Resonances of the Feminine in the Brazilian Christian Religions -- Chapter 18 Faith and Feminism: Resolving the Gender Issue through Mythology and Archetype -- Chapter 19 Feminist, Womanist, and Mujerista Theologies in Conversation -- Chapter 20 Confucianism and Feminism -- Chapter 21 Men Are Not Yang and Women Are Not Yin: Gender Construction in the Tao Te Ching and the I Ching -- Chapter 22 American Muslim Women and Faith-Inspired Activism -- Chapter 23 Special Women in the Holy Quran -- Chapter 24 Feminism and the Future of Religion.